การเรียนการสอนแบบมอนเตสซอรี่ - ศรีสุข, ชมภูนุช; จำเริญสาร, วงศ์ชนก (วารสารการบริหารการศึกษา มมร.วิทยาเขตร้อยเอ็ด, 2024)
บทความนี้มีวัตถุประสงค์เพื่อให้เห็นความสำคัญในจัดการเรียนการสอนแบบมอนเตสซอรี่ (Montessori Education) ซึ่งเป็นการจัดประสบการณ์สำหรับเด็กปฐมวัย ที่มีความจำเป็นและสำคัญ เนื่องจากเด็กปฐมวัยหรือช่วงระยะ 6 ปีแรกของชีวิต เป็นช่วงที่สติปัญญา และพลังจิตของคนเราจะพัฒนาได้สูงสุด และการสอนแบบมอนเตสซอรี่เป็นการเน้นให้เด็กทำกิจกรรมด้วยตนเอง มีเสรีภาพในการหาความรู้ตามความสนใจ เรียนรู้จากประสบการณ์ตรง ผ่านการสังเกต และลงมือทำ ดังนั้นจึงควรส่งเสริมการเรียนรู้อย่างถูกวิธีพร้อมทั้งเตรียมความพร้อมให้เหมาะสมตามวัย เพื่อให้มีพัฒนาการที่เหมาะสมตามวัย เพื่อจะส่งผลให้เด็กนั้นโตไปเป็นผู้ใหญ่ที่มีคุณภาพ การจัดประสบการณ์ตามแนวคิดของมอนเตสเตอรี่สำหรับเด็กปฐมวัยนั้นเป็นการจัดประสบการณ์จากสิ่งแวดล้อมที่ใกล้ตัวเด็กให้เด็กได้เรียนรู้อย่างอิสระ และเลือกกิจกรรมที่เขาสนใจเองได้ ผ่านสิ่งแวดล้อมที่ครูจัดให้อย่างมีเป้าหมาย ผ่านประสาทสัมผัสทั้ง 5 ได้แก่ ตา หู จมูก ลิ้น และมือ ไม่เน้นการท่องจำ ห้องเรียนแบบมอนเตสซอรี่นี้จะจัดสภาพแวดล้อมที่คล้ายกับบ้าน มีห้องต่าง ๆ เช่น ห้องนอน ห้องโถง ห้องครัว แม้กระทั่งสวนให้ได้ออกไปนั่งเล่น ทำกิจกรรมเพื่อซึมซับธรรมชาติด้วย เพราะธรรมชาติเป็นสิ่งแวดล้อมที่สำคัญ เด็ก ๆ ควรได้วิ่งเล่น ปีนป่ายเครื่องเล่นสนาม ดูแลต้นไม้ใบหญ้า เลี้ยงสัตว์ โดยจะมีครูที่คอยให้คำแนะนำในการเรียน และให้เด็กฝึกทำเองจนเด็กเกิดความเข้าใจและคุ้นชิน จากนั้นเด็กก็จะเริ่มเรียนรู้ด้วยตัวเอง ส่งผลให้เด็กมีสมาธิมากขึ้น เข้าใจมากขึ้น และสามารถจดจำสิ่งต่างๆ ได้อย่างมีประสิทธิภาพยิ่งขึ้น              This article aims to highlight the importance of Montessori Education, which is an experience for early childhood children. that is necessary and important Due to early childhood or the first 6 years of life It is a period of wisdom. and the mental power of people will be developed to the maximum And Montessori teaching emphasizes letting children do activities on their own. Have the freedom to seek knowledge according to your interests. Learn from direct experience Through observation and action, therefore, learning should be promoted in the correct way and prepared appropriately according to age. In order to have appropriate development according to age In order to cause the child to grow up to be a quality adult. Organizing experiences according to the concept of Montesterone for early childhood is organizing experiences from the child's immediate environment for the child to learn independently. and can choose the activities that interest them themselves Through the environment that teachers provide with a goal Through the 5 senses: eyes, ears, nose, tongue and hands. No emphasis on memorization. This Montessori classroom is set up in an environment similar to a home, with rooms such as a bedroom, hall, kitchen, and even a garden to hang out in. Do activities to absorb nature as well. Because nature is an important environment, children should be able to run and play. Climbing on playground equipment Take care of the trees, grass, and animals. There will be teachers who will give advice on studying. And let the children practice doing it themselves until the children understand and are familiar with it. Then the child will begin to learn on his own. As a result, children can concentrate more. understand more and can remember things more efficiently.